A variabilidade populacional do elemento de transposição mariner na espécie Drosophila simulans e sua descoberta em Drosophila melanogaster - Steiner, Camila Gomes (2009)
Transposable elements are DNA sequences that can change their location within the genome and can be found in almost all organisms. The mariner transposable element belongs to Class II, Tc1-mariner superfamily. An inactive insertion of this element in the gene white (w+) located on the X chromosome, causes a phenotypic change in color's eyes becoming them a peach color in the place of the wild coloration, being for this reason called whitepeach (wpch). Crossing of mutant females with males obtained from nature, an offspring with eyes the color of peach or variegated with spots of wild color is formed enabling estimate transposicional activity in natural populations. From the use of this system, several studies have been performed to understand if the number of copies and the activity of the mariner element are involved with environmental factors, historical and/or populational. In this study, the existence of intrapopulation variability of D. simulans collected in two places at Santa Maria (RS) city was investigated by crossing with a line of D. simulans wpch. Moreover, data on another species, D. melanogaster, were also obtained and analyzed: interspecific crosses generated progeny with variegation. The isolines that showed these properties were studied using of molecular research tools, such as PCR, cloning and sequencing, it was also necessary. The results suggest the existence of intrapopulation variability in D. simulans and indicate the discovery of sequences very similar to the element mariner in the genome of natural populations of D. melanogaster.